2020
DOI: 10.5588/ijtld.19.0684
|View full text |Cite
|
Sign up to set email alerts
|

Reasons why patients with tuberculosis in South Korea stop anti-TB treatment: a cross-sectional study

Abstract: BACKGROUND: As there had been no reduction in the TB burden in South Korea since 2000, a public-private mix (PPM) strategy was launched in 2011. The purpose of this study was to investigate the reasons for lost to follow-up (LTFU) among TB patients and their clinical characteristics.METHOD: A multicentre, cross-sectional study based on in-depth interviews with patients and their families by TB specialist nurses was conducted. Patients who were reported with a final outcome of LTFU in 2015–2017 at all PPM hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 0 publications
0
21
0
1
Order By: Relevance
“…A key aspect of this approach is to provide counselling and education to all TB patients as described in the Clinical Standards. 71 , 98 AEs are a frequent cause of poor adherence, treatment interruption and loss to follow-up. 99 Patients who are aware of potential AEs may be more likely to notify their healthcare team, facilitating more timely management of AEs, potentially reducing the severity of AEs and preventing unfavourable outcomes.…”
Section: Standardmentioning
confidence: 99%
See 1 more Smart Citation
“…A key aspect of this approach is to provide counselling and education to all TB patients as described in the Clinical Standards. 71 , 98 AEs are a frequent cause of poor adherence, treatment interruption and loss to follow-up. 99 Patients who are aware of potential AEs may be more likely to notify their healthcare team, facilitating more timely management of AEs, potentially reducing the severity of AEs and preventing unfavourable outcomes.…”
Section: Standardmentioning
confidence: 99%
“… 115 117 When redesigning a TB register, it is recommended to capture data on personalised dosing and TDM, to include a set of core variables which are essential to describe, measure and evaluate the cascade of care in adults, as well as children. 98 Individual data are preferred over aggregated data, but this depends on the local arrangements. As systematic evaluation of drug dosing, as well as of AEs, is relatively easy with the implementation of computerised, individual registers, this should be considered.…”
Section: Priorities For Future Researchmentioning
confidence: 99%
“…Therefore, the paper by Kim et al in this issue of the Journal is relevant and timely. 3 The study describes the reasons for LTFU in 94,872 patients treated in public-private mix (PPM) hospitals in South Korea, where 2957 or 3.1% were LTFU. Out of the surveyed and selected LTFU patients, three major groups emerged based on the reason for abandoning treatment.…”
mentioning
confidence: 99%
“…Kim et al reports that one third of the LTFU group was over 65 years of age and linked with adverse events, whereas the younger LTFU patients were more likely to have treatment experience and/or prior negative outcomes. 3 A large global study on adverse events in the treatment of MDR-TB showed that 75% of the patients experiencing side effects had a median age below 53. 4 This indicates that education about TB treatment and prevention of side effects needs to be prioritised, and measures for their management implemented.…”
mentioning
confidence: 99%
See 1 more Smart Citation